Revision of the Neotropical species of Trichacis Foerster (Hymenoptera: Platygastroidea: Platygastridae), with description of 24 new species - Arias-Penna, Tania Milena; Masner, Lubomir; Delsinne, Thibaut (Zootaxa, 2012)
The hymenopteran genus Trichacis is presumed to be endoparasitoid of Cecidomyiidae. Only three species of this genuswere hitherto recognized in the Neotropical region. Here, twenty four (24) new species are described based on 145 specimens: T. acarinata (Costa Rica), T. acuminata (Bolivia), T. acuta (Colombia), T. clypeata (Costa Rica), T.colombiana (Colombia), T. concavata (Costa Rica), T. corrugata (El Salvador, Mexico), T. costaricana (Costa Rica), T.delsinnei (Costa Rica), T. depressa (Costa Rica), T. dianae (Colombia, Ecuador, Venezuela), T. fernandezi (Ecuador), T.hansoni (Brazil, Costa Rica, Nicaragua, Panama), T. kaulbarsi (Mexico), T. magnifica (Mexico), T. mexicana (Mexico),T. panamana (Panama), T. pecki (Ecuador), T. procera (Mexico), T. proximata (Costa Rica), T. punctata (Brazil), T.sculpturata (Mexico), T. transversata (Costa Rica), and T. triangulata (Mexico). A key for males and females of the 27 Neotropical species is provided.